The mediator role of perceived social support in the relationship between difficulties in emotion regulation and suicide tendency - Demir, Berkan; Sumer, Zeynep Hatipoglu; Demir, Berkan (Springer, 2023)
While literature maintained a strong association between emotion regulation skills and suicidal behavior, relatively less is known as to what extent this relationship goes through different dimensions of perceived social support. The purpose of the present study is to examine the possible mediator role of divergent aspects of perceived social support (family, friends, and significant other) in the relationship between difficulties in emotion regulation and suicide tendency. Conveniently selected 641 college students (430 female, 211 male) living in the different regions of Turkey constituted the sample of the present study. The findings indicated that perceived family, friends, and significant other support mediated the relationship between difficulties in emotion regulation and suicide tendency, with perceived family support being the strongest mediator. The entire model explained 51% of the variance in suicide tendency among college students. Regarding suicide tendency, males reported significantly higher scores than females. Our findings underscore that although difficulties in emotion regulation posed a significant risk factor for suicide tendency, perceived social support from family, friends, and significant other remained resilience factors that highlight the need to promote university students' social support systems.
Keywords: Suicide; Perceived Social Support; Difficulties In Emotion Regulation; Structural Equation Modeling; Turkey